Mpox after COVID-19 in Africa: Different epidemic, similar challenges - Gloria P. Gómez-Pérez; Shem O.O. Sam; Nicaise Ndembi; Tobias F. Rinke de Wit (Journal of Public Health in Africa)
Africa faces again a new outbreak of mpox, heavily burdening the Democratic Republic of Congo (DRC). Factors such as biological and ecological changes in the virus, waning of immunity to smallpox, socio-economic challenges, and global economic strain are fueling this epidemic. To analyse the drivers of the mpox outbreak in DRC, review the international and local response, and draw lessons from the COVID-19 pandemic to propose strategies for building epidemic-resilient healthcare systems in the region. The focus is on the DRC, where the mpox epidemic is concentrated, and the broader African region, assessing both rural and urban healthcare contexts. This study synthesises epidemiological data, global health policies, and local health system responses. Key insights are drawn from COVID-19 case studies, and assessment of access to diagnostics and vaccines. The DRC hosts over 95% of Africa’s mpox cases, with significant challenges in human-wildlife interactions, poverty, and weakened healthcare systems exacerbated by COVID-19. Vaccine shortages, diagnostic delays, and uneven international support reflect a repeat of challenges seen during COVID-19. Localised vaccine and diagnostics production, improved risk communication, and digital health tools are highlighted as critical interventions. An epidemic-resilient healthcare framework, leveraging local production of medical products, regulatory empowerment, and real-time data collection, is essential for controlling mpox and future outbreaks. This study underscores the need for African-led solutions, addressing socio-economic drivers, enhancing local capacities, and fostering international solidarity to mitigate future epidemic threats.